Knowledge and comprehension about health risk and safe radiographic techniques among the dental students of Vivekanandha Dental College For Women - A cross-sectional study - Jennifer Monisha Rajan; Kavya Ganesh Kamaraj; Girish R Shavi; Shankar Shanmugam; Senthil Kumar Sennan; Lalithambigai Gunasekaran (Wolters Kluwer Medknow Publications, 2023)
Introduction: Ionizing radiation has biological health hazards. Increased level of ionizing radiation has both stochastic and deterministic effect. Aim: The aim of the current study was to evaluate the knowledge, approach, and insight of the biological ill effects of dental X-ray and appropriate radiation safety measures among the female dental students from Tiruchengode and to compare it between the preclinical and clinical students. Settings and Design: This study was conducted at Vivekanandha Dental College for Women, Tiruchengode, a cross-sectional study. Materials and Methods: The current study was performed among 202 female dental students of Tiruchengode. The knowledge, approach, and insight about radiation safety were gathered by questionnaire survey. The questionnaire pertained to biological ill effects and radiation safety measures in the form of multiple choice was given to each subject through an online survey. Statistical Analysis Used: Descriptive analysis was performed. Mann-Whitney U-test was used to analyze the difference between the different answers of preclinical and clinical students. Results: The overall correct response was 39.14% and it was noted in descending order from clinical students to preclinical students. Conclusions: Thus, there is a vast difference in knowledge and awareness between the preclinical and clinical dental students. Moreover, this clearly shows that continuing education of radiology risk effects should be stressed, especially among female dental students, since they attain different milestones in their lives right from puberty.